الخدمات المصرفية في البنوك الإسلامية : بنك التضامن الإسلامي الدولي في اليمن نموذجا /‏ - زعيمي، أمين قائد محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study aims to examine the Islamic legal application in the banking services in Islamic banks, and find out what types of banking services are offered by Islamic banks. The aim is to arrive at a deep understanding of the reality of the services provided to people in the field of Islamic banking today. It aims to remain with the Islamic legal rule concerning these services, and the scholars' teachings on the reality of Islamic banking services, and know the truth about banking services provided by the riba-based banks. It also aims to clarify the difference between the banking services offered by Islamic banks and banking services offered by traditional banks. The study entails a detailed discussion on the principles of Islamic banking services, and an investigation of the banking credit “financing” as financial instruments for investment. It investigates in how far these tools in Islamic banks are different from other banks. It also studies Islamic banking services and the reality of the practical applications of contemporary banking services in the field of banking business, whether banking services, credit based or not, and states the determinants of legitimacy that frame the work of the banking services offered by banks to the people. It explains the reality of some banking services developed in the Al- Tadamon International Islamic Bank, and its practical applications in the Bank, and specifies the Islamic legal rule in these questions. The study followed the analytical critical method for the theoretical side, and an evaluative critical approach, which dealt with the practical study of Al- Tadamon International Islamic Bank as a model. The study adopted the hypothesis that the Islamic banks paid no attention to the legitimacy of some Islamic banking services in their non credit dealings In this light, the researcher arrives at a numbers of results, among them; that the findings of this research are in agreement with the preceding idea that the Islamic banks in Yemen do not consider the Islamic legal legitimacy of some Islamic banking services other than in limited specific cases, and the Islamic banks in Yemen dependence on commercial law to offered some non- credit banking services. Also, there are some non- credit banking services which the Islamic banks in Yemen do not offer, although the environment with a big number of citizens who are not inclined to interact with traditional banks, based on an Islamic perspective, is favorable.